LANGUAGE AND CULTURE: THEIR INTERRELATIONSHIP - Bekchanova Mahliyoxon Hamidjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Language  and  culture  are  inseparable  components  of  human  society  that influence  and  shape  one  another.  Language  functions  not  only  as  a  means  of communication but also as a carrier of cultural values, traditions, beliefs, and social norms.  Through  language,  individuals  express  their  identities,  preserve  cultural heritage,  and  transmit  knowledge  across  generations.  At  the  same  time,  cultural environments  influence  the  structure,  meaning,  and  use  of  language.  In  the  era  of globalization, understanding the relationship between language and culture has become increasingly  important  for  effective  communication,  language  education,  and intercultural cooperation. This article examines the interrelationship between language and culture, highlighting their mutual influence on communication, identity formation, education, and social development. Furthermore, the study emphasizes the significance of cultural awareness in foreign language learning and intercultural communication in the modern world.